An English language needs analysis of obligatory English preparatory program students at İstanbul Sabahattin Zaim Universtiy - Kar, İsa (İstanbul Sabahattin Zaim Üniversitesi, Sosyal Bilimler Enstitüsü, Yabancı Diller Eğitimi Anabilim Dalı, 2014)
This study intended to investigate the English language needs of the Obligatory Preparatory program students at IZU. In order to identify the perceived needs, the data were gathered from three different groups of informants; that is, 50 freshmen, 20 sophomores, and 10 departmental instructors at IZU. The three groups, from their own point of views, responded to a 25-item structured questionnaire consisting of five categories, the need for English, four language skills and sub-skills, instructional materials, competence of the instructors at the prep department and focus on departmental terminology. The data for this study were collected via questionnaires and were analyzed through SPSS.17. In this study, three kinds of questions in the questionnaires were used. One of them is Likert-scale whose mean scores and standard deviations were calculated and then arithmetic mean of each item is given at the end. Second question type is multiple choice questions and the third one is closed-ended questions both of which the frequencies and percentages were taken. Also, as in the Likert-scale questions, arithmetic means of multiple choice questions and closed-ended questions were given at the end. After the analysis it was understood that speaking and writing skills should be given more importance, field terminology should be given by specialists and a summer course with shorter hours should be offered to learners so that they should not forget English during summer holiday. Also, cooperation between departments and prep program should be enhanced to meet students' language needs better.

Bu çalışmayla İstanbul Sabahattin Zaim Üniversitesinin zorunlu İngilizce hazırlık program öğrencilerinin İngilizce Dili gereksinimlerinin saptanması amaçlanmıştır. Bu gereksinimlerin saptanabilmesi için üç farklı kaynak grup kullanılmıştır. Bu kaynak gruplar 50 adet birinci sınıf öğrencisi, 20 adet ikinci sınıf öğrencisi ve 10 adet bölüm öğretim elemanlarından oluşmaktadır. Sözü edilen üç gruba 25 adet soru maddesinden oluşan bir anket uygulanmıştır. Her bir anket maddesi kendi içerisinde numaralandırılmamış alt maddeleri barındırmaktadır. Anket soru maddeleriyle İngilizce öğrenmenin gereksinimi, yabancı dil becerileri ve alt becerileri, hazırlık öğretmenlerinin yeterliliği, hazırlık programında kullanılan eğitim araç ve gereçlerinin öğrencilerin beklentilerini ne kadar karşıladığı ve öğrencilere alan dilinin terminolojisinin ne kadar verilip verilemediğidir. Ankette üç tür soru çeşidinden yararlanılmıştır. Bunlardan birincisi Likert tipi soru ölçeğidir. Bu ölçekteki soru türlerinin ortalama skorları ve standart sapmaları bulunmuştur. İkinci soru türü çoktan seçmeli sorular ve üçüncü soru tipi is kapalı uçlu soru türleridir. Bu soru türlerinin ise frekans ve yüzdelikleri alınmıştır. Ayrıca bu üç soru türününde aritmetik ortalama değerleri oluşturulan tablolarda verilmiştir. Uygulanan analizler sonucunda şu bulgulara varılmıştır. Hazırlık eğitiminde konuşma ve yazma becerilerine daha fazla önem verilmeli, alan terminolojisi uzman kişiler tarafından verilmeli, yaz tatilinde öğrencilere yıl boyunca öğrendiği dili unutmaması için ders sayısının daha az olduğu bir İngilizce yaz kursu sunulmalıdır. Ayrıca, öğrencilerin dil ihtiyaçlarının daha iyi karşılanması için bölüm hocaları ve hazırlık hocalarının arasındaki işbirliği artırılmalıdır.
İstanbul Sabahattin Zaim Üniversitesi zorunlu yabancı dil hazırlık programı öğrencilerinin İngilizce dili ihtiyaç analizi
Introduction -- Rationale of the Study -- Statement of the Problem -- Research Questions -- Significance of the Research -- Outline of the Study -- Limitations of the Study -- Definitions of Terms -- Needs Analysis -- Definition of Needs -- Needs Analysis and Needs Assessment -- Functions of a Needs Analysis -- Problems in Needs Analysis -- The Necessity of Conducting a Needs Assessment